Dual Inhibition of PARP and the Intra-S/G2 Cell Cycle Checkpoints Results in Highly Effective Radiosensitization of HPV-Positive HNSCC Cells - Hintelmann, Katharina; Berenz, Thomas; Kriegs, Malte; Christiansen, Sabrina; Gatzemeier, Fruzsina; Struve, Nina; Petersen, Cordula; Betz, Christian; Rothkamm, Kai; Oetting, Agnes; Rieckmann, Thorsten (Frontiers in Oncology, 2021)
In head and neck squamous cell carcinoma (HNSCC), tumors positive for human papillomavirus (HPV) represent a distinct biological entity with favorable prognosis. An enhanced radiation sensitivity of these tumors is evident in the clinic and on the cellular level when comparing HPV-positive and HPV-negative HNSCC cell lines. We could show that the underlying mechanism is a defect in DNA double-strand break repair associated with a profound and sustained G2-arrest. This defect can be exploited by molecular targeting approaches additionally compromising the DNA damage response to further enhance their radiation sensitivity, which may offer new opportunities in the setting of future de-intensified regimes. Against this background, we tested combined targeting of PARP and the DNA damage-induced intra-S/G2 cell cycle checkpoints to achieve effective radiosensitization. Enhancing CDK1/2 activity through the Wee1-inhibitor adavosertib or a combination of Wee1 and Chk1 inhibition resulted in an abrogation of the radiation induced G2 cell cycle arrest and induction of replication stress as assessed by γH2AX and chromatin-bound RPA levels in S phase cells. Addition of the PARP inhibitor olaparib had little influence on these endpoints, irrespective of checkpoint inhibition. Combined PARP/Wee1 targeting did not result in an enhancement in the absolute number of residual, radiation induced 53BP1 foci as markers of DNA double-strand breaks but it induced a shift in foci numbers from S/G2 to G1 phase cells. Most importantly, while sole checkpoint or PARP inhibition induced moderate radiosensitization, their combination was clearly more effective, while exerting little effect in p53/G1 arrest proficient normal human fibroblasts, thus indicating tumor specificity. We conclude that the combined inhibition of PARP and the intra-S/G2 checkpoint is a highly effective approach for the radiosensitization of HPV-positive HNSCC cells and may represent a viable alternative for the current standard of concomitant cisplatin-based chemotherapy. In vivo studies to further evaluate the translational potential are highly warranted.